Role of Mitogen-Activated Protein Kinase Pathways in Multifactorial Adverse Cardiac Remodeling Associated with Metabolic Syndrome - Asrih, Mohamed; Mach, François; Nencioni, Alessio; Dallegri, Franco; Quercioli, Alessandra; Montecucco, Fabrizio (Mediators of Inflammation, 2013)
Metabolic syndrome has been widely associated with an increased risk for acute cardiovascular events. Emerging evidence supports metabolic syndrome as a condition favoring an adverse cardiac remodeling, which might evolve towards heart dysfunction and failure. This pathological remodeling has been described to result from the cardiac adaptive response to clinical mechanical conditions (such as hypertension, dyslipidemia, and hyperglycemia), soluble inflammatory molecules (such as cytokines and chemokines), as well as hormones (such as insulin), characterizing the pathophysiology of metabolic syndrome. Moreover, these cardiac processes (resulting in cardiac hypertrophy and fibrosis) are also associated with the modulation of intracellular signalling pathways within cardiomyocytes. Amongst the different intracellular kinases, mitogen-activated protein kinases (MAPKs) were shown to be involved in heart damage in metabolic syndrome. However, their role remains controversial. In this paper, we will discuss and update evidence on MAPK-mediated mechanisms underlying cardiac adverse remodeling associated with metabolic syndrome.